Effects of high fructose diet on lipid metabolism and the hepatic NF-κB/ SIRT-1 pathway. (2nd January 2022) - Iskender, Hatice; Yenice, Guler; Terim Kapakin, Kubra Asena; Dokumacioglu, Eda; Sevim, Cigdem; Hayirli, Armagan; Altun, Serdar
ABSTRACT: The liver is the primary site for fructose metabolism; therefore, the liver is susceptible to fructose related metabolic disturbances including metabolic insulin dysfunction, dyslipidemia and inflammation. We investigated whether astaxanthin (ASX) can modify hepatic nuclear factor-kappa B (NF-κB)/sirtuin-1 (SIRT-1) expression to alter oxidative stress caused by ingestion of excess fructose in rats. The animals were divided randomly into two x two factorially arranged groups: two regimens were given either water (W) or 30% fructose in drinking water (F). These two groups were divided further into two subgroups each: two treatments, either orally with 0.2 ml olive oil (OO) or 1 mg ASX/kg/day in 0.2 ml olive oil (ASX). Fructose administration increased serum glucose, triglycerides and very low density lipoproteins, and decreased serum concentration of high density lipoproteins; fructose did not alter serum total cholesterol. Excess fructose decreased hepatic superoxide dismutase (SOD) and increased hepatic NF-κB and MDA levels. ASX treatment increased hepatic SIRT-1 and decreased hepatic NF-κB and malondialdehyde (MDA) levels. ASX treatment decreased hepatic NF-κB and increased SOD levels, but did not alter MDA level in rats fed high fructose. ASX administration ameliorated oxidative stress caused by excess fructose by increasing hepatic NF-κB and SIRT-1 expression.